Development and Evaluation of Hesperetin- Loaded Solid Lipid Nano-particles - Prakash, Ravi; Bhardwaj, Manoj (Journal of Neonatal Surgery, 2025)
The present research was based on the Development and Evaluation of Hesperetin- Loaded Solid Lipid Nano-particle. The hesperitin was obtained from the Sigma-Aldrich, India. Stearic acid, Span 20, Tweens 80 (Sigma Aldrich, India), distilled water, ethanol were procured from the local chemical shop in Haridwar, UK. In Preformulation studies, various parameters i.e., organoleptic properties, melting point, solubility, Drug excipients compatibility studies and Preparation of Standard Calibration Curve. Preparation of gallic acid- based solid lipid nanoparticles was done using spray-drying method. It was characterized for various parameters i.e., Physical appearance, Entrapment efficiency, Drug content determination, pH determination, Determination of particles size & PDI, SEM analysis, In vitro drug release and Stability studies. Hesperitin showed very poor solubility in distilled water and ethanol. Both stearic acid and cholesterol dissolved it freely. Formulations F1-F6 were observed to be clear, white and homogenous in appearance. After 6 hours, SLN 1, SLN 2, SLN 3 showed % drug release as 89.3±0.4, 92.6±0.3 and 91.4±0.2, respectively. While SLN 4 demonstrated increased % release as 92.9±0.2 %. In conclusion, among the several forms of solid lipid nanoparticles of hesperitin, F5 was found to be the most significant formulation in terms of in-vitro drug release, droplet size, and drug content. It also showed improved stability, with no significant change in pH, % drug release and physical appearances after being stored for a month.